A hybrid grid connected / solar energy converter for micro-co-generation - Oei, Wilson (2010)
The analysis of static conversion electronics system for photovoltaic solar energy processing with real commercial application is presented this report. The system is particularly simple and robust, using low cost technology. The power electronics is divided in three stages. The first one carries out the batteries charge control and the panels operate in the MPP (Maximum power point). The second stage, carried out by a boost converter that is responsible to step-up the input voltage. The third stage is the feedback circuit that consists of PWM controller to make sure the output is always constant. Feedback controls are used to regulate the output. Experimental results are presented to compare their closed-loop performances. This project will focus on the design and implementation of a DC to DC converter which will take an input voltage of 11.4 to 12.6Vdc and output a constant 24Vdc.